FOLLOW-UP OF METHOTREXATE EFFECTIVENESS IN A PATIENT WITH JUVENILE POLYARTHRITIS - L. A. Balykova; O. M. Soldatov; N. V. Shchekina; A. V. Krasnopol'skaya; A. N. Os'kina (Педиатрическая фармакология)
The article presents a short review of the current notion of the leading role methotrexate in treatment of most clinical variants ofjuvenile idiopathic arthritis. The authors demonstrate that methotrexate is a “gold standard” of antirheumatic therapy and the key disease-modifying drug of pediatric rheumatology. The emphasis is laid on safety profile and advantages of parenteral administration thereof. The article presents follow-up of a clinical case involving use of dosage form of methotrexate in the dose of 15 mg/m per week for subcutaneous administration in a patient with polyarticular juvenile idiopathic arthritis featuring insufficient effectiveness and low tolerance of the oral drug. Prescription of methotrexate for subcutaneous administration helped to terminate progression of the disease and pain syndrome and improve function of the affected joints and the patient’s quality of life.